Scenario-based actions to upgrade small-scale furniture producers and their impacts on women in Central Java, Indonesia - Purnomo, H.; Irawati, R.H.; Fauzan, A.U.; Melati (2011)
Indonesian furniture accounts for almost 1% of the global furniture trade, valued at more than USD 135 billion. In many countries, including Japan, European countries and Indonesia, women make decisions about selecting which furniture to buy. In Central Java’s Jepara District – the centre of teak furniture production in Indonesia – annual furniture exports are valued at USD 120 million. However, the roles of small-scale producers and women workers in furniture industry are weak. Though women workers play an important role in generating revenue, they are paid less than men. They are also less powerful and exercise less control over resources, decision making, product development and bargaining. Action research and value chain analysis were used to improve small-scale producers and women workers. This paper explores different scenarios for upgrading small-scale producers, such as participation in trade exhibitions, training programmes and producer associations and their effects on women workers.